Study of Impact of COVID-19 on Mental Health and Wellbeing of Staff Working in a Forensic Mental Health Service - Heather Baker; Sikander Singh Gill; Anne Aboaja; Swapan Kole; Amanda E. Perry (Psych, 2022)
This study explored the impact of COVID-19 on the mental health and wellbeing and trust support of Tees Esk and Wear Valleys (TEWV) NHS forensic staff using an online google survey during the second wave of the pandemic. Survey respondents were a voluntary cross-sectional sample of 246 TEWV staff working in the forensic directorate staff; this included males (n = 60, 24.5%); with the majority of staff aged between 36–50 years (n = 99, 40.2%) and 50 years or older (n = 80, 32.5%). The results showed that staff working at home and on the front line were both affected by depression, stress and anxiety. Those most at risk were younger staff members. We concluded that the mental health and well-being of staff working should be a priority. It is important to consider targeted support that should be aimed at younger staff members to provide an open culture enabling for those who want support to have readily available signposted resources. Staff working in different settings may have experienced a different impact of COVID-19 on their mental health and wellbeing, and whilst some interventions might be successfully applied across the service, it would be beneficial to understand the unique needs of staff working in specific settings.